Femoral malalignment after gamma nail insertion in the lateral decubitus position - Abubeih Hossam M.A. (SICOT-J, 2018)
Introduction: Insertion of gamma nail with the patient in lateral decubitus position have the advantages of easier access to the entry point, easier fracture reduction and easier implant positioning. Our study described the incidence of femoral angular and rotational deformity following gamma nail insertion in lateral decubitus position. Methods: In a prospective clinical case series, 31 patients (26 males and 5 females; the average age of 42.6 years) with 31 proximal femoral shaft fractures that were treated with gamma IMN were included in our study. Postoperatively, computerized tomography scans of the pelvis and both knees (injured and uninjured sides) were examined to measure anteversion angles on both sides. A scout film of the pelvis and upper both femurs was taken to compare the neck shaft angles on both sides. Results: No angular malalignment was detected in our series; the mean angular malalignment angle was 1.6 ± 1.5°. There was a high incidence of true rotational malalignment of ≥10° in 16 out of 31 patients (51.6%); most of them were external rotational malalignment. Younger age group (≤40 years) had significantly more incidence of rotational malalignment (≥10°) than older age group (>40 years) (P-value 0.019). Discussion: Gamma nail fixation in lateral decubitus position without the fracture table gives an accurate and easier access to the entry point, good implant positioning with no or minimal angular malalignment (varus −valgus) but poses high incidence of true rotational malalignment. Great care and awareness of rotation should be exercised during fixing proximal femoral fractures in lateral decubitus position.